POST-SURGICAL COMPLICATIONS IN PATIENTS WITH CERVICAL SPONDYLOTIC MYELOPATHY - GUTIÉRREZ,LUIS MARIO ALTAMIRANO (2017)
ABSTRACT Objective: To identify the incidence and type of postoperative hospital complications in patients with cervical spondylotic myelopathy (CSM) treated by anterior approach, and to describe comorbidities present in patients who had complications. Methods: Retrospective, observational, descriptive cohort study of secondary sources (medical records), over a period of 3 years. We included 180 cases treated by anterior approach, excluding revision surgeries. Results: There was an incidence of complications of 11.11% (20 cases), with no statistically significant difference between sexes. The main complication was pneumonia (50%), associated to prolonged intubation (40%), followed by neurological impairment (20%). In the hospital outcome he was found most often to another hospital discharge (65%, 13 cases). The main comorbidity was systemic arterial hypertension (31.58%, p = 0.46), followed by smoking (26.32%, p 0.10). Conclusions: The highest hospital incidence of postoperative complications was found in patients with CSM treated by anterior approach in relation to that reported in the literature. There was a high incidence of airway complications not correlated with soft tissue edema or hematoma in more than half of the cases. The incidence of airway complications shows an area of opportunity to improve extubation protocols and management of the airways in post-surgical special care unit. Level of Evidence III. SIRELCIS Registry: R-2014-3401-5. Study conducted without commercial support.